A Low‐Cost, Self‐Standing NiCo2O4@CNT/CNT Multilayer Electrode for Flexible Asymmetric Solid‐State Supercapacitors. (24th July 2017) - Wu, Peng; Cheng, Shuang; Yao, Minghai; Yang, Lufeng; Zhu, Yuanyuan; Liu, Peipei; Xing, Ou; Zhou, Jun; Wang, Mengkun; Luo, Haowei; Liu, Meilin
Abstract : The demand for a new generation of flexible, portable, and high‐capacity power sources increases rapidly with the development of advanced wearable electronic devices. Here we report a simple process for large‐scale fabrication of self‐standing composite film electrodes composed of NiCo2 O4 @carbon nanotube (CNT) for supercapacitors. Among all composite electrodes prepared, the one fired in air displays the best electrochemical behavior, achieving a specific capacitance of 1, 590 F g −1 at 0.5 A g −1 while maintaining excellent stability. The NiCo2 O4 @CNT/CNT film electrodes are fabricated via stacking NiCo2 O4 @CNT and CNT alternately through vacuum filtration. Lightweight, flexible, and self‐standing film electrodes (≈24.3 µm thick) exhibit high volumetric capacitance of 873 F cm −3 (with an areal mass of 2.5 mg cm −2 ) at 0.5 A g −1 . An all‐solid‐state asymmetric supercapacitor consists of a composite film electrode and a treated carbon cloth electrode has not only high energy density (≈27.6 Wh kg −1 ) at 0.55 kW kg −1 (including the weight of the two electrodes) but also excellent cycling stability (retaining ≈95% of the initial capacitance after 5000 cycles), demonstrating the potential for practical application in wearable devices. Abstract : A self‐standing and flexible capacitor electrode ( 24.3 µm thick) of NiCo2 O4 @carbon nanotube (CNT)/CNT, fabricated by a simple, cost‐effective process, displays excellent volumetric capacitance ( 870 F cm −3 ). An all solid‐state supercapacitor based on this composite film electrode demonstrates high energy density ( 27.6 Wh kg −1 ) at 0.55 kW kg −1 while maintaining good cycling stability.